PENGARUH PENGGUNAAN MEDIA ENSIKLOPEDIA BERBASIS AUGMENTED REALITY TERHADAP MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Marshanawiah, Andi; Rifda Mardian Arif; Gamar Abdullah; Meylan Saleh (JAMBURA Elementary Education Journal, 2025)
Quality education requires innovative approaches to enhance student motivation, particularly in challenging subjects like spatial geometry. One technology that can support this is Augmented Reality (AR), which allows students to interact directly with three-dimensional objects. This study aims to examine the effect of an AR-based encyclopedia media on student motivation in elementary school learning. The research adopts a Pre-experimental design with a One-Group Pretest-Posttest Design approach, involving 13 fifth-grade students from SDN 20 Pulubala, Gorontalo, as the sample. Data were collected through motivation questionnaires, observations, and documentation. The findings indicate that the use of AR media significantly improves student motivation. Prior to the intervention, most students showed low to moderate motivation, but after using AR, the majority demonstrated increased motivation, reaching very high and high levels. A paired sample t-test revealed a significant difference in motivation before and after the intervention (p ≤ 0.05). Based on these findings, it can be concluded that the use of AR-based encyclopedia media is effective in enhancing student motivation, positively impacting their understanding of spatial geometry. This study also contributes to the development of technology-based educational curricula to improve the quality of learning in elementary schools.